Considerations for prevention of and emergency response to tularemia outbreaks in Ukraine: vaccine involvement - Saunders, David L.; Pierson, Benjamin C.; Zlenko, Oksana; Gelhaus, H. Carl (Frontiers in Bacteriology, 2024)
Tularemia is a highly dangerous, febrile zoonotic bacterial infection, endemic to many regions of the Northern hemisphere including Eastern Europe. The current war in Ukraine raises the risk for both natural outbreaks of tularemia resulting from destroyed infrastructure, and potential use as a weapon of war or bioterrorism. There has been a substantial history of outbreaks in prior wars in the region, and tularemia has been previously weaponized and stockpiled as an offensive agent. There are current reports of "mouse fever", where Russian soldiers are affected with a high fever associated with mice in the battlefield. While antibiotic countermeasures to naturally occurring forms of tularemia are available, these may not be appropriate for long-term risks on the battlefield and could contribute to antibiotic resistance. At this time, there are no FDA or EMA approved tularemia vaccines, which are an ideal alternative to antibiotic prophylaxis. Vaccines have advantages in not requiring diagnosis, are generally safe and effective, leading to long-lasting prophylaxis with little impact to the patient and little need for future medical intervention. The potential for engineered forms of the disease for deliberate use may limit the effectiveness of existing countermeasures. The sporadic nature of outbreaks, and likely outcomes following deliberate use raise a number of complexities in a potential emergency response. Means to optimize potential countermeasure assessment, including responsible and effective vaccine candidate testing are discussed.